Analysis Of The Influence Of Product Quality, Price And Brand Image On Skintific Skincare Purchase Decisions Among Students - Imdillah, Imdillah; Anwar, Suhardi M; Pajarianto, Hadi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study investigates the impact of factors like product quality, price, and brand perception on the purchasing habits of students in the Management Program at Muhammadiyah University of Palopo, particularly in relation to Skintific skincare products. Methodology: Using a quantitative approach, data were collected via questionnaires distributed to 100 respondents, chosen purposively from a population of 1,287 students. The data were analyzed through multiple linear regression techniques. Results: The results reveal that product quality alone does not have a significant effect on purchasing decisions. However, price and brand image have a strong positive and statistically significant influence. Together, these three factors show a considerable combined impact. Findings: Although product quality is not the main driver, it helps reinforce the effects of price and brand image. For students, price sensitivity and brand perception generally outweigh product quality in shaping their purchasing behavior. Originality: This study offers original insights by focusing specifically on the student market segment in skincare product purchasing behavior, highlighting how price and brand image outweigh product quality, a perspective that has been underexplored in prior research. Â Conclusion: he study emphasizes the importance of marketing strategies that focus on competitive pricing and strong brand development to effectively influence students' purchasing decisions. Type of Paper: Original research article.